Device selection for carotid stenting: reviewing the evidence. (3rd October 2017) - Setacci, Carlo; Mele, Mariagnese; de Donato, Gianmarco; Mazzitelli, Giulia; Benevento, Domenico; Palasciano, Giancarlo; Setacci, Francesco
ABSTRACT: Introduction : Carotid artery stenting (CAS) has recently changed the status in the treatment of the extracranial carotid atheromasic disease. In recent years, evolution in both stents and protection devices as well as in carotid stenting techniques, has resulted in an important reduction in the rate of stroke in patients undergoing CAS procedures. Areas covered : The purpose of this article is reviewing the literature and summarizing the current evidence of the new available materials to underline the importance of the correct choice of the devices during the procedure. Expert commentary : Certainly a key issue in order to limit the periprocedural events to the lowest possible, is to select the appropriate device for the appropriate patient anatomy and clinical syndrome, the so called 'tailored approach'.